Atypical (symplastic) uterine leiomyoma masquerading as endometrial malignancy in a 78-year-old post-menopausal Nigerian woman - John Nwadiokwu; Elizabeth Grillo; Victor Okebalama; Olutomiwa Omokore; Obinna Onwe; Aaron Uka; Jennifer Ibhiedu; Samuel Okore; Nneoma Nwanna; Chiomaefuelim Dibie (Babcock University Medical Journal)
Abstract